Remote Works : managing for freedom, flexibility, and focus - Greene, Ali; Sanderson, Tamara (Oakland, CA : Berrett-Koehler Publishers, Inc., 2023)
"Two veteran remote managers draw on their pre- and post-COVID experience to offer pragmatic, proven advice for designing remote work environments where everyone thrives. Since the pandemic began, a staggering 64 million American workers have experienced working full-time from home. In 2020 and 2021, quick-fix solutions and emergency-transition plans allowed organizations to survive with remote work. Now Ali Greene and Tamara Sanderson want to show managers how to design positive, flexible virtual work cultures that will thrive in the long term-because remote work is here to stay. Drawing on their years of experience working for all-remote companies DuckDuckGo and Automattic (the parent company of WordPress) and as international digital nomads, Greene and Sanderson have written the ultimate design-thinking handbook for managing remote and hybrid teams. The book addresses challenges such as managing conflict, establishing norms, communicating effectively, reframing productivity, and creating an authentic team culture. Using practical, hands-on exercises, they give managers the confidence to design and prototype optimal remote work structures for their teams. Greene and Sanderson never said the remote work world is easy, but they've seen firsthand that it can be effective and enjoyable. Now it's time for others to reap the benefits. Reading group discussion guide is available in the book"--
Includes bibliographical references and index.
Keywords: Virtual work teams -- United States; Communication in management -- United States; Organizational change -- United States